Mental Help-seeking Intention Among Rural Sarawak Bumiputera Adolescents : the Application and Extension of the Theory of Planned Behaviour - Muhammad Najib, Hasan @ Ahmad; Jeffery, Stephen; Noorzilawati, Sahak (Universiti Putra Malaysia (UPM), 2025)
Introduction: Mental health problem is part of the human life experience. Currently, 12% of Malaysian adolescents suffer from mental health problems. According to the National Health Morbidity Survey 2015, adolescents of rural Sarawak and Bumiputera ethnicity had the highest prevalence of mental illness among all other states; however, their help-seeking behaviour remains unknown. The study's purpose was to apply the new extended Theory of Planned Behaviour (TPB) and structural equation modelling to identify which were the strongest predictor in determining mental help-seeking intention among the Bumiputera ethnic adolescents in the rural area of Sarawak. Materials and methods: The research was conducted using a cross-sectional design, with a self-administered questionnaire using multistage cluster sampling. Results: The report will be based on the study conducted among 1267 Indigenous ad olescents in the rural area of Sarawak, with a response rate of 84.5%. The partial mediation model of the extended Theory of Planned Behaviour, explained 19.2% of the variance in the study. The current model explained the rural Bumiputera Sarawak adolescent's help-seeking intention and indicated that attitude, subjective norm, and perceived behavioural control are the main predictors of adolescent help-seeking intentions. Conclusion: Any intervention planned for adolescents in rural areas of Sarawak concerning mental health should be based on the Theory of Planned Behaviour model, promote the positive benefit of mental health services, and create a supportive environ ment toward mental health in the community.